Analisis Persepsi Dan Tanggapan Literasi Digital Dalam Proses Pembelajaran Di SDN 79 Palembang - Rizka Syafitri; Rani Apira; Santi Rizkiana; Noviani; Adam Helnsiki Umar (Advances In Education Journal, 2025)
To prepare students to face the challenges of the 21st century, elementary schools need to teach digital literacy from an early age. This study aims to analyze the perceptions and responses of digital literacy in the learning process at SDN 79 Palembang and its obstacles. The method used is a descriptive qualitative approach through observation, interviews, and questionnaires. The results of the study indicate that the principal, three class teachers, and 30 students from grades IV-VI, amounting to 89.3%, actively use ICT tools, digital media, and interactive platforms in the learning process. The school also has a computer laboratory, projector, and internet access as supporting facilities. The results indicate that perceptions and responses of digital literacy influence learning outcomes, increasing creativity, participation, independence in learning, and forming critical, ethical, and responsible digital characters.